Typology of e-commerce shoppers: the case of COVID-19 - Ramadan, Zahy (2023)
Purpose The spread of coronavirus disease (COVID-19) has drastically changed the entire market structure and shopping behaviors across the world. While shoppers rushed toward e-commerce platforms during the pandemic, the key debate that rose was on how this behavior will evolve post COVID-19. The purpose of this study was to explore the different categories of e-commerce platforms’ users and propose a distinctive customer typology in the era of the COVID-19 pandemic. Design/methodology/approach An exploratory qualitative research design was adopted because of the novelty of the subject. In total, 43 participants were interviewed, including 27 consumers and 16 experts in the field of e-commerce. Findings Based on the findings, this study distinguishes between two stages of e-commerce usage during the pandemic. Furthermore, this study identifies four key typologies of e-commerce shoppers that are expected to form at the end of the coronavirus: duty-bound, e-watcher, makeshift and onli-vorous shoppers. The characteristics and businesses strategies pertaining to each of the identified groups are discussed. Originality/value To the best of the authors’ knowledge, this research is among the first to identify the different stages, while proposing an innovative typology of e-commerce platform post COVID-19. This study also offers useful recommendations to deal with similar future crises.